Identity politics in turkey in the process of EU membership - Sarışen, Gamze Rezan (My University, 2005)
This MA thesis is an analysis on the positive role of the European Union (EU) and the EU-Turkey relations in terms of Turkey in solving its identity related problems and consolidating its democracy since the Helsinki summit of December 1999. The main focus of this study will be on Turkey's changing political attitude towards its official identity politics in the process of EU membership. The starting point is that recent improvements in Turkey's democratic order would not have been possible, at least at such a rapid pace, without such a strong EU membership goal. In this respect, it is argued that the combination of internal demands of different segments of Turkish population, and the demands of external desired object for Turkey, that is the EU, created an environment that is favorable to the relaxation of the monolithic Kemalist conception of Turkish national identity. Since the early 1990s, Turkish national identity has been increasingly challenged from many fronts however these internal dynamics by themselves could not create the desired outcome of opening up the national identity on a less monolithic conception. In the post-Helsinki period, as the integration process of Turkey with the EU has intensified, Turkish authorities have become more sensitive to the internal dynamics of the country. In this context, with the strong EU membership prospect, the recent reform process clearly highlights the fact that Turkey for the first time in its Republican history is likely to move in the direction of redefining its official identity politics outside the Kemalist understanding of national identity.

Bu tez çalışması, Türkiye'nin resmi adaylık statüsü kazandığı Aralık 1999 Helsinki Zirvesinden itibaren, Avrupa Birliği (AB) ve Türkiye-AB ilişkilerinin Türkiye'nin resmi kimlik politikalarında karşılaştığı problemleri çözme ve demokratik yapısını güçlenlendirme konularında oynadığı olumlu rol üzerine bir analizdir. Bu çalışmada, AB üyelik süreci ile beraber, Türkiye'nin resmi kimlik politikaları ile ilgili değişen siyasi yaklaşımı üzerinde durulacaktır. Türk siyasi hayatı ve demokrasisinde yaşanan son dönemdeki olumlu gelişmelerin, ülkenin iç dinamiklerinin de bu dönüşüme uygun bir ortam sunmasına rağmen, güçlü bir AB üyelik perspektifi olmadan, en azından bu kadar kısa bir süre içinde gerçekleşemeyeceği bu çalışmanın başlangıç noktasını oluşturmaktadır. Bu bağlamda, Türk toplumunun değişik kesimlerinden gelen değişim taleplerinin, Türkiye'nin AB üyelik amacıyla birleşmesi, tekçi Kemalist ulusal kimlik nosyonunun tartışılabilmesini mümkün kılan bir siyasi atmosferin oluşmasına zemin hazırlamıştır. 1990'ların başından itibaren Kemalist milliyetçilik anlayışına karşı eleştirel sesler her ne kadar artsa da, bu eleştirileri dile getiren kesimler tartışmayı arzulanan çoğulcu demokratik düzeye çekmeyi başaramamışlardır. Helsinki zirvesi sonrası ise, Türkiye ve AB bütünleşmesinin ivme kazanmasıyla birlikte, Türk politik çevreleri Türkiye'deki bu mevcut iç dinamiklere daha hassas hale gelmişlerdir. Bu bağlamda, son reform sureci, güçlü AB üyelik perspektifiyle beraber, Türkiye'nin Cumhuriyet tarihinde ilk defa kesmi kimlik politikalarını, Kemalist ulusal kimlik anlayışının dışında bir yaklaşımla ele almaya başladığını göstermektedir.
Keywords: Avrupa Birliği_Dış İlişkiler_Türkiye; Türkiye_Dış İlişkiler_Avrupa Birliği